128k views
0 votes
-3x + y = -6 Y= 1/2x-1

-3x + y = -6 Y= 1/2x-1-example-1

1 Answer

4 votes

Answer:

Explanation:

Given system of equations in the question are,

-3x + y = -6

y =
(1)/(2)x-1

We can rewrite these equation as,

-3x + y = -6

y = 3x - 6 ------(1)

Table of input-output values for this equation will be,

x 0 1 2 3 4

y -6 -3 0 3 6

y =
(1)/(2)x-1 ------(2)

Table for this equation will be

x 0 2 4 6 8

y -1 0 1 2 3

By plotting these points on the graph we find (2, 0) is a common point in both the tables,

Therefore, (2, 0) is the only one solution of the given system of equations.

User Sumanth
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.